Pengaruh Pembiasaan Dzikir Terhadap Ketenangan Belajar Santri Pondok Pesantren Modern Al-Ishlah Bondowoso - abdul wafi; Musleh; Ramadhan, Fahim Abu; Septiadi, Septiadi; Prasetiya, Benny (Educational Research Center, 2026)
The phenomenon of increasing psychological pressure among santri due to the density of academic and spiritual activities necessitates effective interventions based on religious approaches. This study aims to analyse the effect of habitual dhikr practice on learning tranquillity among santri at Al-Ishlah Modern Islamic Boarding School, Bondowoso. This quantitative study employs an associative approach with a sample of 100 santri from grades 4, 5, and 6 of Kulliyatul Muballighien Al-Islamiyah (KMI). Data were collected using a Likert-scale questionnaire (1–5) and analysed through validity and reliability tests, as well as simple linear regression using SPSS version 25. The results indicate that habitual dhikr practice has a positive and significant effect on learning tranquillity (R² = 0.47; t = 6.85; p < 0.001). These findings suggest that consistent dhikr practice is capable of reducing academic stress levels and enhancing the emotional stability of santri. This study strengthens transcendental psychology theory, which positions dhikr as a mechanism of spiritual self-regulation. Practically, these results may serve as a foundation for the development of spiritual mindfulness programmes within Islamic boarding school environments.